(3GdJShjb GdeHGTQ h GdYdGbGJ GdYGeI (B/s - (3YHjOGJ, eMeO GHQGgjes ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3ebOeI aj GdJShjb GdeHGTQ , GdHQjO GdeHGTQ (B: (3GdGgOGa h GdechfGJ h GdGYJHGQGJ , GdGTcGd GdGYdGfjI GdeWhdI h JUejegG h JfXjegG , GdGTcGd GdGYdGfjI GdbUjQI , GdSLdGJ h GdHWGbGJ h GdhSGFd GdHOjdI , , GYdGfGJ GdJShjb GdeHGTQ (B: (3GdGMLGe h GdGfhG Y h GdhSGFd h GdJUeje h GdJfajP , GdJShjb GdeHGTQ GdGdcJQhfj (B((3GdGPGYI h GdJdaRjhf h GdJShjb Yf HYO (B)(3, GdJShjb GdeHGTQ h GdGfJQfjJ , JWHjbGJ GdJShjb GdeHGTQ ddeSJgdcjf h GdeTQhYGJ , GdJShjb GdeHGTQ ddNOeGJ h GdeYdheGJ , JShjb bhGYO GdHjGfGJ h GdJQhjL ddGSJaSGQGJ , GdJShjb GdeHGTQ ddeDSSGJ ZjQ GdQHMjI h bjGS GdfJGFL , bjGS fJGFL GdJShjb GdeHGTQ h eJGHYJgG , fTCI h JWhQ GdYdGbGJ GdYGeI h GdJShjb GdeHGTQ , GdJfXje GdOGNdj ddYdGbGJ GdYGeI , JNWjW GdYdGbGJ GdYGeI aj GdeDSSGJ , GdYdGbGJ GdYGeI aj GdbWGYjf GdYGe h GdNGU (B.s
(3eQGLY U(B.285s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdYdGbGJ GdYGeIs